Stimulating students’ creativity in speaking through film discussion - HMC, Sri Fauziah; Intan Hamzah (International Journal of Research in Education, 2025)
This research explores the role of film-integrated activities in stimulating high school students' creativity in spoken communication through structured film discussions. Employing an experimental design, eleventh-grade students were divided into two groups, with the experimental group participating in guided discussions based on the short film The Buddy. Pre- and post-intervention assessments evaluated student performance in grammar, vocabulary, fluency, pronunciation, and comprehension. The results indicated significant improvements in speaking proficiency following the intervention, as confirmed by statistical analyses. These findings underscore the effectiveness of using films as authentic instructional tools that not only enhance speaking skills but also foster student creativity. The study highlights the pedagogical value of integrating multimedia materials into language instruction to promote more dynamic and communicative learning environments.